Tanggung Jawab Guru PAK dalam meningkatkan Prestasi Belajar Peserta Didik Usia 7-12 Tahun - Cici Pramita; Filmon Berek (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The teaching profession is a unique profession because many skills are needed to carry out one's duties in preparing future generations. The ideal teacher is not only one who fulfills the requirements, e.g. for example, he may be smart and skilled or an expert in his field of knowledge, but most importantly, the teacher must be able to position himself as an agent of change. Therefore, the Christian teacher must assume personal, social, intellectual, moral and spiritual roles and responsibilities. The responsibility of the Christian religion teacher as an educator is to encourage, teach, lead, guide, train, assess and evaluate students to achieve the expected learning objectives and learning outcomes. Jesus as an example for Christian religion teachers should be the standard for every Christian educator. Therefore, it affects work during learning and leads to achievement for students. The responsibility of a Christian religious education teacher is to improve student learning achievement and provide learning motivation in order to achieve an achievement for each student. From this writing, the author uses qualitative as a literature study and is supported by several references from books, journals for the completeness and refinement of writing. This. This study resulted in a conclusion that the responsibility of a teacher greatly influences the achievement of each student in the world of education.